2013
DOI: 10.4236/aasoci.2013.34025
|View full text |Cite
|
Sign up to set email alerts
|

Social and Economic Factors Influencing Buruli Ulcer Health Seeking Decision Making in the Ga West and South Municipalities

Abstract: Background: Buruli ulcer infection is generally referred to as a re-emerging disease with the highest burden in West Africa. In Ghana, about 1000 cases are reported annually. The former Ga district (now the Ga West and Ga South municipalities) continues to report the highest proportion of the worst ulcerated wounds in Ghana, despite various interventions implemented. The aim of this study was to determine factors affecting treatment-related decision making in BU affected families. Methods: Semi-structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Furthermore, it was anticipated that Christians and Muslims, based on their religious beliefs, religion should have a positive association with the knowledge on BU, however, this study found that religion was not statistically associated with the knowledge of the participants on BU. Another study corroborated the findings of this study and identified that although the majority of respondents stated the hospital as the place for appropriate treatment, some BU victims preferred witchdoctors/herbalists and prayers, and considered the hospital as the last option which was not statistically significant [11].…”
Section: Association Between Knowledge and Demographic Characteristic...supporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, it was anticipated that Christians and Muslims, based on their religious beliefs, religion should have a positive association with the knowledge on BU, however, this study found that religion was not statistically associated with the knowledge of the participants on BU. Another study corroborated the findings of this study and identified that although the majority of respondents stated the hospital as the place for appropriate treatment, some BU victims preferred witchdoctors/herbalists and prayers, and considered the hospital as the last option which was not statistically significant [11].…”
Section: Association Between Knowledge and Demographic Characteristic...supporting
confidence: 81%
“…Although the study showed a colossal (68.2%) failed to report at the health facility, 78% admitted that the health facility could manage their condition better. This has been confirmed in a study which found that access to health services encouraged timely treatment of Buruli ulcer patients [11].…”
Section: Availability Of Drugs and Diagnostic Materials For Buruli Ul...mentioning
confidence: 74%
See 1 more Smart Citation
“…The socio-demographic characteristics of the study area has remained virtually the same as was reported in earlier studies [12,15,17,18,26], where the Ga ethnic groups were dominant with majority of them identifying with the Christian religion with primary level education. The knowledge of the disease was very high among respondents, gained mostly through the experiences of knowing someone with the infections.…”
Section: Discussionmentioning
confidence: 63%
“…However, it has been reported that community-based interventions could enhance case detection and reduced treatment dropout and defaulter rates [17, 18]. …”
Section: Introductionmentioning
confidence: 99%